Effectiveness of Tizanidine and intensive rehabilitation in Spastic Cerebral Palsy (Bangladesh Journal of Medicine, 2023)
Background: The treatment of cerebral palsy is multifactorial. The aim of the study is to find out the efficacy of tizanidine and intensive rehabilitation in the treatment of spastic cerebral palsy.Methods: This observational study was conducted over 35 patients in Sir Salimullah Medical Mitford Hospital from January 2022 to December 2022.The patients satisfying the inclusion and exclusion criteria were enrolled: total 35 patients received tizanidine (2mg) orally at a dose of 1 mg given at bed time under 10 years and 2 mg given at bed time more than 10 years of age, then after 1 week maintenance dose was given at 0.3 mg/kg/day, three times daily in combination with intensive rehabilitation 1 hour daily five times a week. Total 24 weeks of intensive rehabilitation was given. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks.Results: The study shows high efficacy in reducing tone in spastic cerebral palsy measured by using Modified Ashworth scale (p